SENI DRAMA SEBAGAI MEDIA DAKWAH PADA SANTRI PONDOK PESANTREN WALI SONGO PURWOSARI PASURUAN - Muhammad Sofiullah; A. Khairuddin; Mokhammad Baharun (Fakultas Dakwah Universitas Ibrahimy, 2024)
Dramatic art as a medium for da'wah is a form of applying da'wah bil hal as is usually done in the Wali Songo strategy for spreading Islam. The Wali Songo Islamic Boarding School, Purwosari Pasuruan, uses dramatic arts as education and a medium to convey d a'wah messages. This research was motivated by the design and delivery of a da'wah message through dramatic art which was quite interesting and relevant to the students of the Wali Songo Islamic Boarding School, Purwosari Pasuruan. Therefore, the aim of th is research is, first, to find out the design of dramatic art as a medium for preaching to the students of the Wali Songo Islamic Boarding School, Purwosari Pasuruan. Second, to describe the process of conveying da'wah messages through dramatic art as a me dium for da'wah to the students of the Wali Songo Islamic Boarding School, Purwosari Pasuruan. The research method in this scientific work, the author uses a qualitative research method with a case study type. Meanwhile, this type of research uses descript ive qualitative by conducting in - depth observations and interviews with the research object. The design and implementation of this dramatic art is by quoting storylines or scripts from several books after recitation with Islamic boarding school caregivers and displayed at khitobah activities every Friday with Jamiyyah Farhaniyyah. Meanwhile, the targets of the da'wah for the dramatic ... ....... Vol. 6 No. 1 Januari 2024 Jurnal Komunikasi & Konseling Islam | 2 arts performance activities are the students of the Wali Songo Islamic Boarding School, Purwosari Pasuruan, who they usually call performing the Koran arts. The conclusion of this research is that the design for preparing dramatic arts is to recite the yellow book with Islamic boarding school teachers and then review the material from the book that has been studied into a drama script by holding a script review with the director and the players/actors. Meanwhile, the process of conveying da'wah messages through the art of drama applied by the students of the Wali Songo Islamic Boarding School is by conveying words of wisdom in bo oks that have been studied and discussed by emphasizing the elements of speech (vocals), expressions or facial expressions, as well as acting. and play a role.